Investor Sentiment and Stock Market Response to Earnings News - Mian, G. Mujtaba; Sankaraguruswamy, Srinivasan (The Accounting Review, 2012)
ABSTRACT We examine whether market-wide investor sentiment influences the stock price sensitivity to firm-specific earnings news. Using the recently developed measure of investor sentiment by Baker and Wurgler (2006), we find that the stock price sensitivity to good earnings news is higher during high sentiment periods than during periods of low sentiment, whereas the stock price sensitivity to bad earnings news is higher during periods of low sentiment than during periods of high sentiment. This influence of sentiment is especially pronounced for the earnings news of small stocks, young stocks, high volatility stocks, non-dividend-paying stocks, and stocks with extremely high and low market-to-book ratios. Further analysis suggests that the sentiment-driven mispricing of earnings contributes to the general mispricing of stocks due to investor sentiment. JEL Classifications: D14; D21; G24.